Nanoparticle Applications in Carbon Capture: Emerging Opportunities in Climate Change Mitigation - Nidaa Yaseen Taha; Hanan Abdul Qader Abdulilah (Indonesian Journal on Health Science and Medicine, 2026)
General Background: The tourism sector increasingly relies on strategic alliances to address competitive challenges and share resources in dynamic markets. Specific Background: In this context, human resource management practices, particularly recruitment and training strategies, are central to building the competencies required for managing partnerships among tourism companies in Baghdad. Knowledge Gap: Despite the growing importance of alliances, many organizations emphasize legal and financial aspects while overlooking the role of qualified human capital in managing cooperative relationships. Aims: This study aims to analyze the relationship between recruitment and training strategies and the efficiency of strategic tourism alliances. Results: Using a descriptive-analytical approach and survey data from 93 respondents, the findings reveal a significant positive relationship between recruitment and training strategies and alliance efficiency, with a correlation coefficient of 0.800 and an explanatory power of 63%. Technical and behavioral training emerged as the most prominent dimension, while all dimensions showed statistically significant contributions. Novelty: The study integrates human resource management functions with strategic alliance performance in the tourism sector within the Baghdad context. Implications: The findings suggest that adopting competency-based recruitment and specialized training programs supports cooperation, reduces organizational conflicts, and contributes to achieving shared objectives in tourism alliances. Highlights:• Recruitment Practices Based on Competencies Support Alignment of Shared Goals• Training Programs Strengthen Cooperation and Reduce Organizational Conflicts• Technical and Behavioral Skills Show the Strongest Contribution to Alliance Performance Keywords: Recruitment Strategies, Training Programs, Strategic Alliances, Tourism Companies, Human Resource Management.